DARK SIDE OF QUARK BAG MODEL - Brilenkov, Maxim; Eingorn, Maxim; Jenkovszky, Laszlo; Zhuk, Alexander (Одеські астрономічні публікації, 2013)
We calculate the present expansion of our Universe endowed with relict colored objects - quarks and gluons - that survived hadronization either as isolated islands of quark-gluon nuggets or spread uniformly in the Universe. The QNs can play the role of dark matter